Leading indicators of Euroland business cycles - Ulrich Fritsche; Felix Marklein (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
The introduction of a common monetary policy in eleven European countries increased the need for leading indicators for that area. A reliable leading indicator should possess the following properties: (1) The movements in the indicator series should resemble those in the business cycle reference series. (2) The relation between the reference series and the indicator should be statistically significant and stable over time. (3) The inclusion of the indicator in out-of-sample forecasting procedures should improve the predictive power. Our analysis deals with tests for these requirements applied to Euroland data. We use frequency domain analysis, Granger-causality tests and out-of sample forecasts. Only a few indicators pass all tests, while the non-monetary indicators perform best. – – Die Einführung einer gemeinsamen Geldpolitik in elf europäischen Ländern erhöhte die Bedeutung von konjunkturellen Frühindikatoren für dieses Gebiet. Brauchbare Frühindikatoren sollten folgende Eigenschaften besitzen: (1) Die konjunkturellen Bewegungen des Frühindikators sollten denen der Referenzreihe folgen. (2) Die Beziehung zwischen den Reihen sollte stabil und signifikant sein. (3) Die Einbeziehung des Indikators sollte die Out-of-sample-Prognose verbessern. Unsere Untersuchung testet diese Anforderungen für Euroland-Daten. Dazu werden Methoden der Spektralanalyse, verschiedene Granger-Kausalitäts-Tests und Out-of-sample-Prognosen verwendet. Nur wenige Indikatoren bestehen die Tests auf die geforderten Eigenschaften, wobei die nichtmonetären Indikatoren besser abschneiden.
Keywords: 330; Konjunkturindikator; Europäische Wirtschafts- und Währungsunion; Statistischer Test; Schätzung; EU-Staaten